(+)-Discodermolide: A Marine Natural Product Against Cancer. (2004) - De Souza, Marcus Viníus Nora
Abstract : (+)-Discodermolide was isolated in 1990 by Gunasekera et al. from the deep-water Caribbean sponge Discodermia dissoluta. It attacks cancer cells in a similar way to the successful cancer drug Taxol® that has become the best-selling anticancer drug in history. Taxol is also the first natural product described that stabilizes the microtubules involved in many aspects of cellular biology and that represent an important target of anticancer chemotherapeutics. However, (+)-discodermolide appears to be far more potent than Taxol® against tumors that have developed multiple-drug resistance, with an IC50 in the low nanomolar range. Due to these excellent results, this natural product was licensed to Novartis Pharmaceutical Corporation in early 1998. The present review covers the history, biological activity, total synthesis, and synthetic analogs of (+)-discodermolide.